Penerapan Metode Double Moving Average dalam Memprediksi Permintaan Kayu - Denny Irawan; Raja Tama Andri Agus; Sahren Sahren (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
UD. Tunas Meranti Kuala Tanjung is a business engaged in the manufacture of furniture. Problems faced by UD. Tunas Meranti is difficult to predict the demand for the type of wood that customers want for furniture making, so it is difficult to determine which type of wood should be in stock every month. If the supply of wood exceeds demand then storage costs will increase. The risk is that wood that is stored for too long will become dry, hard and difficult to process. To maintain business continuity, a wood supply strategy is needed, namely by making predictions (forecasting). The purpose of this research is to be able to predict the demand for wood types so that business owners can provide wood types according to customer needs. The method used in this study is the Double Moving Average method in order to minimize the chance of errors between predictions and actual data. To be more efficient, the author designed a web-based forecasting system and uses a MySQL database. The conclusion from the prediction results of meranti wood demand for the next period is 43 sticks with a MAPE value of 8% and mahogany wood is 19 sticks with a MAPE value of 11%, which means that the prediction using the DMA method is very effective.